Pengaruh Kegiatan Bermain terhadap Kemandirian Anak di TK Negeri Pembina Kecamatan Kota Utara Gorontlo - Siti Fadila Rajulali; Elsya Usman; Putri Desriyanti Ahmad; Wintriyanti Sanawali; Sulastya Ningsih (Prodi Sastra Jepang Universitas Ngudi Waluyo, 2025)
This study was conducted to identify the extent to which play activities influence the independence of group B children aged 4–6 years at Pembina State Kindergarten, North Kota District. The method used was a quantitative approach with an experimental design, involving 15 children as samples. Data collection was carried out through observation, questionnaires, and documentation, then analyzed using descriptive statistics and simple linear regression tests. The results of the study showed that play activities have a significant impact on increasing children's independence. Various forms of play such as obstacle courses, writing along the lines, and free play provide opportunities for children to manage themselves, make simple decisions, demonstrate responsibility, and try new challenges. Aspects of social independence were also seen to develop through children's abilities to share, cooperate, and tidy up play equipment. These findings confirm that play activities are not merely recreational activities, but also effective learning tools to support the development of early childhood independence. Therefore, play activities are worthy of being implemented as a meaningful learning strategy in increasing children's independence in a kindergarten environment.